(untitled) (Journal of Fiber Bioengineering and Informatics, 2018)
A two steps direct polymerization process was developed. The first step is to produce oligomer and then the oligomer of lactic acid is polymerized with binary catalyst tin chloride dihydrate/ p-toluenesulfonic acid. In this way, the direct synthesis of poly (lactic acid)(PLLA) without any organic solvents was investigated. The properties and structures of products were characterized by nuclear magnetic resonance (NMR), FT-IR spectra, and so on. The results show that comparatively high molecular weight polymer of lactic acid can be prepared by direct processing under appropriate technological conditions and that the melt polymerization of PLLA behaviors are as the second-order reaction mechanism.